An Insight on the Inconsistency of the Theoretical Construction of Avant-garde Concept in 20th-Century Art - Fortuny-Agramunt, Jaume (Advances in Social Sciences Research Journal, 2023)
This paper analyses avant-garde art theory through the concept of originality, understood as shock. The initial hypothesis is that this theoretical construction is a misunderstanding because it neglects the body during the experience lived before the work of art. It reminds us that if we are aware of our presence, it is thanks to the fact that we are psychosomatic individuals. Even so, we tend to evaluate the work of art from philosophical reflection rather than from analysing the form that excites us. It shows how the materialisation of the work of art sought by the avant-garde should have destroyed our cognitive baggage. It concludes that it only succeeded in initiating a tendency in art towards rhetoric that reaches the present day, where theoretical constructions are the only works of art. The emptiness of this avant-garde art theory concerning the touching causes its inconsequentiality, being left without any other pretension as only art. The author relies on the fact that we understand ourselves as people through our subjection to what we see to make us understand that looking without feeling is a contradiction.